Injury risk in British Columbia, Canada, 1986 to 2009: are Aboriginal children and youth over-represented? - George, M Anne; Jin, Andrew; Brussoni, Mariana; Lalonde, Christopher E; McCormick, Rod (Injury epidemiology, 2015)
Background Children and youth worldwide are at high risk of injury resulting in morbidity, disability or mortality. Disparities in risk exist between and within countries, and by sex and ethnicity. Our aim is to contribute data on disparities of injury rates for Aboriginal children and youth compared with those of the general population in British Columbia (BC), Canada, by examining risks for the two populations, utilizing provincial administrative data over a 24-year period. Methods Hospital discharge records from the provincial health care database for children and youth were used to identify injury for the years 1986 to 2009. Within the total BC population, the Aboriginal population was identified. Crude rates and standardized relative risks (SRR) of hospitalization were calculated, by year and category of injury type and external cause, and compared to the total BC population for males and females under age 25 years. Results Over the 24-year period, substantive decreases were found in hospitalization injury risks for children and youth in both Aboriginal and total populations, for both sexes, and for most categories and types of injuries. Risk in overall injury dropped by 69% for the Aboriginal population and by 66% for the total BC population, yet in every year, the Aboriginal population had a higher risk than the total BC population. There were over 70% declines in risks among females of intentionally inflicted injury by another, among both the Aboriginal and total BC populations. Risk of injury caused by transport vehicles has decreased by an overwhelming 83% and 72% for the Aboriginal male population and for the total BC male population, respectively. Conclusions The over 70% declines in risks for females of intentionally inflicted injury by another, among both the Aboriginal and total BC populations is excellent news. Risk of injury caused by transport vehicles for males decreased overwhelmingly for both populations. Disparities in rates between the Aboriginal population and total BC population remain because of similarity in the proportional reductions among the two populations. Since the Aboriginal population started at a much higher risk, in absolute terms, the gap between the two populations is shrinking.